A systematic review with meta-analysis of the relation of aflatoxin B1 to growth impairment in infants/children - Behnam Ghorbani Nejad; Zahra Mostafaei; Ali Balouchi Rezaabad; Fatemeh Mehravar; Mahtab Zarei; Azadeh Dehghani; Mohammad Amin Raeisi Estabragh; Somayyeh Karami-Mohajeri; Hamzeh Alizadeh (BMC, 2023)
Abstract Background Aflatoxins are regarded as the most potent genotoxic and carcinogenic type of mycotoxins. This meta-analysis was performed to investigate a the relation of aflatoxin B1 (AFB1) to growth measurements of infants/children, including wasting, underweight, stunting, as well as weight-for-age (WAZ), height-for-age (HAZ), and weight-for-height (WHZ) z-scores. Methods Electronic databases of PubMed, Web of Science, and Scopus were searched to identify related publications. Effect sizes for associations were pooled using the random effects analysis. Subgroup analysis by study design, method used to assess AFB1, and adjustment for covariateswas performed to detect possible sources of heterogeneity. Results Pooled analysis of available data showed that AFB1 exposure was negatively associated growth z-scores, including WHZ (β = -0.02, 95%CI = -0.07 to 0.03), with WAZ (β = -0.18, 95%CI = -0.33 to -0.02), and HAZ (β = -0.17, 95%CI = -0.30 to -0.03) in infants/children. There was a remarkable heterogeneity among studies on WAZ and HAZ (P ≤ 0.001). In prospective cohort studies, AFB1 exposure was found to be significantly associated with the elevated risk of underweight (OR = 1.20, 95%CI = 1.03 to 1.40) and stunting (OR = 1.21, 95%CI = 1.11 to 1.33). Conclusions This meta-analysis highlighted the importance of AFB1 exposure as a potential risk factor for growth impairment in infants/children.